PENGARUH STORE ATMOSPHERE DAN SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING - Sutrisni, Ketut Elly; Martini , Ida Ayu Oka; Niartini, Ni Kadek Wika (Jurnal Magister Manajemen, 2024)
The purchase decision is the ultimate goal of establishing a business to be able to dominate the market and benefit from the business. The purchase decision itself is influenced by several factors, including store atmosphere, quality service and buying interest. The purpose of this study was to determine the factors of purchasing decision determinants based on consumer perception at Nook Restaurant Kerobokan. This research was conducted at Nook Restaurant Kerobokan located at Jalan Umalas 1, Gang Nook No.1, Kerobokan Kelod, by distributing as many as 100 questionnaires to Nook Restaurant Kerobokan consumers. This research is quantitative research with data collection using questionnaire distribution method. The results of this study show that store atmosphere has a positive effect on buying interest, but does not affect purchasing decisions. Furthermore, service quality has a positive effect on purchasing decisions and buying interest. The results of the intervening effect study show that buying interest has a positive influence or strengthens the relationship between variable store atmosphere and quality service on consumer purchasing decisions at Nook Restaurant